1999
DOI: 10.1016/s0092-8674(00)80656-x
|View full text |Cite
|
Sign up to set email alerts
|

CLIP-170 Highlights Growing Microtubule Ends In Vivo

Abstract: A chimera with the green fluorescent protein (GFP) has been constructed to visualize the dynamic properties of the endosome-microtubule linker protein CLIP170 (GFP-CLIP170). GFP-CLIP170 binds in stretches along a subset of microtubule ends. These fluorescent stretches appear to move with the growing tips of microtubules at 0.15-0.4 microm/s, comparable to microtubule elongation in vivo. Analysis of speckles along dynamic GFP-CLIP170 stretches suggests that CLIP170 treadmills on growing microtubule ends, rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
311
2
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(340 citation statements)
references
References 59 publications
26
311
2
1
Order By: Relevance
“…In interphase, GFP-CLIP-170 moved through the cell in cometlike structures at plus ends of growing microtubules (data not shown), consistent with previous observations (Perez et al, 1999). However, we were unable to detect these comet-like structures in mitotic cells transfected with GFP-CLIP-170.…”
Section: Clip-170 Localizes To Microtubule Plus Ends During Mitosissupporting
confidence: 92%
See 1 more Smart Citation
“…In interphase, GFP-CLIP-170 moved through the cell in cometlike structures at plus ends of growing microtubules (data not shown), consistent with previous observations (Perez et al, 1999). However, we were unable to detect these comet-like structures in mitotic cells transfected with GFP-CLIP-170.…”
Section: Clip-170 Localizes To Microtubule Plus Ends During Mitosissupporting
confidence: 92%
“…CLIP-170 is the founding member of the þ TIPs (Perez et al, 1999). It has an N-terminal microtubule-binding domain, a long central coiled-coil domain, required for homodimerization, and a C-terminus with two zinc-finger domains.…”
Section: Introductionmentioning
confidence: 99%
“…CLIP-170 has been proposed to serve the initial docking role, because this protein can interact with both endosomes (Pierre et al, 1992) and the distal ends of microtubules (Rickard and Kreis, 1990). Short arrays of CLIP-170 treadmill at microtubule plus ends as they grow toward the periphery (Perez et al, 1999), providing a potential mechanism for attachment of peripheral endosomes and other structures (Dujardin et al, 1998).…”
Section: Association Of Dynactin and Clip-170 At Microtubule Endsmentioning
confidence: 99%
“…CLIP-170 contributes to the binding of endosomal membranes to microtubules in vitro (Pierre et al, 1992). In cells, CLIP-170 labels the growing ends of microtubules (Perez et al, 1999), an appropriate site for its proposed function. Microtubule binding is regulated by phosphorylation (Rickard and Kreis, 1991), providing a means for release of CLIP-170 (and associated cargo) from microtubules under circumstances in which a static interaction is no longer needed.…”
Section: Introductionmentioning
confidence: 99%
“…GFP fusion proteins of each revealed that they track the plus-ends of growing microtubules in cells [4,5]. At the amino terminus of CLIP-170 are two tandem CAP-Gly microtubule binding domains [6].…”
Section: Introductionmentioning
confidence: 99%